2017
DOI: 10.1007/s41463-016-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic Management and Living Wages: a Case of Compelling Connections?

Abstract: The balance between employee pay and human thriving remains theoretically and empirically under-explored at the lower-end of the wage and income spectrum. Poverty Trap theory and the Law of Diminishing Returns offer seemingly contradictory predictions of the relationship between thriving and wages. An exploratory survey of low-and middleincome earners from a range of occupations was used to test these competing possibilities by relating hourly wage rates to thriving as measured by sense of (i) work happiness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 55 publications
5
35
0
Order By: Relevance
“…Rupp et al [15] stated that, "Organizational justice has been identified as one of the more dominant and frequently studied topics in industrial-organizational psychology, organizational behavior, and human resource management" (p. 919). Despite this broad support, there is an acknowledgement that the psychology field understands less about those at the bottom of the pay spectrum, for example [2]. Carr et al [16] noted that, "Work may be a panacea for poverty, but the world of work in 2018 is characterized by 'Working Poverty'" (p. 901), reinforcing the point that our understanding of workers in low paying jobs is poor.…”
Section: Pay Fairnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Rupp et al [15] stated that, "Organizational justice has been identified as one of the more dominant and frequently studied topics in industrial-organizational psychology, organizational behavior, and human resource management" (p. 919). Despite this broad support, there is an acknowledgement that the psychology field understands less about those at the bottom of the pay spectrum, for example [2]. Carr et al [16] noted that, "Work may be a panacea for poverty, but the world of work in 2018 is characterized by 'Working Poverty'" (p. 901), reinforcing the point that our understanding of workers in low paying jobs is poor.…”
Section: Pay Fairnessmentioning
confidence: 99%
“…We understand little about the psychology of working poverty [1], including the psychology of transitioning from it toward more sustainable livelihoods [2]. In particular, linkages between "employee pay and human thriving remain theoretically and empirically under-explored at the lower-end of the wage-and-income spectrum" [2] (p. 215). Compounding this gap in our understanding is an under-representation of countries outside of the United States [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a fourth original paper, a group of researchers of the poverty research group at Massey University, New Zealand explore humanistic management and its related policy dimensions (Carr et al 2017). Specifically, Stuart Carr, Jane Parker, James Arrowsmith, Jarrod Haar, and Harvey Jones explore the question of a living wage.…”
Section: Overview Of Contributions To This Issuementioning
confidence: 99%